HUBUNGAN KEBIJAKAN DIVIDEN (DIVIDEND PAYOUT RATIO DAN DIVIDEND YIELD) TERHADAP VOLATILITAS HARGA SAHAM DI PERUSAHAAN-PERUSAHAAN YANG TERDAFTAR DI BURSA EFEK INDONESIA - Andreas Widhi Khurniaji; Surya Raharja (Diponegoro Journal of Accounting, 2013)
This study aims to analyze the effect of dividend policy to share price volatility in non-finance companies listed on IDX in the period of 2009 to 2011. The indicators of dividend policy are dividend payout ratio (DPR) and dividend yield. Analysis in this study also use the other factors guessed have any influences both on dividend policy and share price volatility, that are : size, earning volatility, leverage and growth. Share price volatility is measured by baskin method. Documentary data (secunder) from financial statements and/or annual reports is used in this study. This study’s population is non-finance companies that listed on IDX from 2009 to 2011 and had an IPO at least on 2004. The sampling method used was purposive sampling, in which there are 70 companies included based on the criterias. Multiple regression is used as the method of analysis. The result of this study shows that only dividend yield has a significant influence to the share price volatility. The higher dividend yield, the less share price volatility, and in adverse. And the control variables that have a significant influence are earning volatility and growth. Both of them have positif influence.